Immune response: the Achilles’ heel of the stem cell-based regenerative therapies - Cláudia S. Oliveira; Freni K. Tavaria (Exploration of Immunology, 2023)
Besides trauma, several pathological conditions which directly affect the normal functioning of organs, require new therapeutic strategies to repair damaged or diseased tissues. Tissue regeneration is a complex and spatiotemporal process involving a plethora of cell types, including various immune cells and stem cells in a synchronized relationship. However, individual parameters, namely ageing, obesity, diabetes, and chronic conditions, have been intrinsically correlated with poor regenerative properties of adult tissues. While vast progress has been made regarding stem cell-based therapy to direct self-healing, the immune response is still the Achilles’ heel of such strategies. Whereas the role of effector immune cells has been well defined along the regenerative process, an understanding of the behavior of the main adult stem cells, namely mesenchymal stem cells (MSCs) and hematopoietic stem and progenitor cells (HSPCs), along the different phases of the regenerative process could clarify how these stem cells can be used to positively influence the immune response. In this scope, this review highlights the main interactions between these stem cells and immune cells during tissue repair, exploring the most important regenerative properties of stem cells and correlating them with the modulation of the immune response during tissue regeneration. Furthermore, the utmost strategies used to explore how the behavior and stem cell fate are affected by specific microenvironments and/or stimuli usually found during a regenerative process, are emphasized. This clarification may provide critical insight into the molecular mechanisms by which stem cells modulate the immune response in a positive feedback loop toward tissue repair.